Personal And Professional Characteristics Of A Good Muslim Doctor: Perception Of Newly Graduated Doctors - Azmi, AN; Jamilah, J; Dzulkhairi, MR; Ramli, S; Ariff, O; Ismail, NMN (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus